2014
DOI: 10.1128/jvi.01540-14
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in the DNA Polymerase Accessory Factor of Herpes Simplex Virus 1 Restores Viral DNA Replication in the Presence of Raltegravir

Abstract: Previous reports showed that raltegravir, a recently approved antiviral compound that targets HIV integrase, can inhibit the nuclease function of human cytomegalovirus (HCMV terminase) in vitro. In this study, subtoxic levels of raltegravir were shown to inhibit the replication of four different herpesviruses, herpes simplex virus 1 (HSV-1), HSV-2, HCMV, and mouse cytomegalovirus, by 30-to 700-fold, depending on the dose and the virus tested. Southern blotting and quantitative PCR revealed that raltegravir inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 41 publications
1
25
1
2
Order By: Relevance
“…42 Compared to HIV-1 viremic women, more women in the HIV-1 aviremic group were currently using raltegravir, although the difference was not statistically significant. There was no correlation between CMV IgG and raltegravir use among HIV-1-positive women currently on cART (data not shown).…”
Section: Clinical Characteristics Of the Study Cohortmentioning
confidence: 95%
“…42 Compared to HIV-1 viremic women, more women in the HIV-1 aviremic group were currently using raltegravir, although the difference was not statistically significant. There was no correlation between CMV IgG and raltegravir use among HIV-1-positive women currently on cART (data not shown).…”
Section: Clinical Characteristics Of the Study Cohortmentioning
confidence: 95%
“…Potential cytotoxic effects of drugs on PK-15 cells were evaluated by assessing cell viability using the CellTiter 96 AQueous One Solution cell proliferation assay (Promega) as described previously (36). Briefly, subconfluent cell cultures grown in 96-well plates were incubated with various concentrations of drugs for 2 h. After incubation for 24 h at 37°C, 20 l of the manufacturer's reagent was added to the cells.…”
Section: Methodsmentioning
confidence: 99%
“…The antiviral drug raltegravir, is an FDA-approved retroviral integrase inhibitor which was recently shown to inhibit replication of the human alphaherpesvirus herpes simplex virus type 1 (HSV-1) (Summa et al, 2008;Zhou et al, 2014). Similar to the anti-herpes nucleoside analogues, raltegravir was also capable of inhibiting FHV-1 replication in the feline corneal explant system.…”
Section: Discussionmentioning
confidence: 99%
“…The retroviral integrase inhibitor raltegravir inhibits FHV-1 replication in both CRFK cells and the whole corneal explant model Based on the recent reports that retroviral integrase inhibitors are also effective against herpesviruses (Yan et al, 2014;Zhou et al, 2014), we decided to explore the potential of this class of antiviral drugs against FHV-1 in the whole corneal explant model. The retroviral integrase inhibitor raltegravir was used as it is currently approved for use in humans for the treatment of human immunodeficiency virus infection (Summa et al, 2008), and was recently shown to be safe for use in cats (Boesch et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation